Counseling To The Women's Farmers Association About Emergency Management In The Community "Training On Cardiopulmonary Resuscitation (Cpr) And Management Of Febrile Seizures - Yenni Elfira; Fatimah Fatimah; Irwadi Irwadi; Iswenti Novera; Ikhsan Amran; Leo Agustigno (Journal of Public Health Indonesian, 2024)
Emergency action is an action that is immediate and occurs at any time, if we are not prepared for this situation then there are not many victims who can be saved. RJP training with basic techniques or what is called Basic Life Support (BLS) or also known as Basic Life Support (BLS) with phantom Resuscitation can increase participants' knowledge significantly even though those given the training are lay people (Putri et al., 2019). Many emergency incidents occur outside hospitals, both due to injuries such as accidents, cardiac arrest and respiratory arrest in the city of Padang. As for community service activities, on June 11 2024, community service was carried out by the women's farmer association organization, through training or counseling, so that the community knew how to properly treat patients with respiratory arrest and cardiac arrest. The aim of community service in the community is to increase knowledge and skills regarding Emergency Management in the Work Environment and Local Environment "Cardiopulmonary Resuscitation Training"